Edible Insects in a Meal: Consumer Acceptability as an Addition to Potential Food Source among Ethnic Restaurants in Metro Manila - Calonge, Richelle; Canzon, Carl Patrick Keann; Garing, Lift Boy; Cabatuando, Hannah Faye (International Journal of Sustainability and Advanced Integrated Research, 2026)
The growing demand for sustainable and alternative food sources has increased interest in the use of edible insects as a viable protein option. This study examined the acceptance of edible insects as an alternative food source in ethnic restaurants in Metro Manila. Specifically, it determined the demographic profile of customers, assessed their level of awareness, willingness to try, and perceived benefits of consuming insect-based food products, and explored the viability of incorporating edible insects into restaurant menus from the perspectives of restaurant stakeholders. A mixed-methods research design was utilized, combining quantitative survey data from restaurant patrons and qualitative interviews with selected stakeholders from ethnic restaurants. Descriptive statistics, inferential analyses, and thematic analysis were employed to interpret the data. Findings revealed that the majority of respondents were aged 18–24 years (65%), female (60%), and college graduates (72%). More than half of the respondents (54%) reported uncertainty regarding prior consumption of insect-based food products or indicated that they had never consumed them. Results showed a moderate level of awareness of edible insects (M = 3.21), while willingness to try insect-based food products was slightly lower (M = 2.89), indicating cautious acceptance. Perceived benefits received relatively higher ratings (M = 3.34), particularly in terms of nutritional value and environmental sustainability. Significant differences were found in perceived benefits and willingness to try when respondents were grouped according to age, income, and prior experience with insect consumption (p < .05), suggesting that demographic factors influence consumer acceptance. Qualitative findings revealed varying levels of stakeholder openness toward adopting edible insects in restaurant operations. Stakeholders recognized opportunities for menu innovation, market differentiation, and alternative protein sourcing; however, concerns regarding supplier reliability, food safety standards, regulatory compliance, and potential consumer resistance were identified. The study concludes that edible insects possess considerable potential as a sustainable food innovation in Metro Manila’s ethnic restaurant sector. Enhanced consumer education, strengthened food safety regulations, reliable supply chains, and strategic product positioning are recommended to improve consumer acceptance and support successful market integration.